An Application of TAM on Use of Remotely Accessible E-Resources of Dhanvantri Library, University of Jammu - Sharma, Bindu; Arti Thakur, Reenu; Sharma, Diksha (Journal of Information and Knowledge, 2023)
This study examines how remote users used electronic resources made available by the Dhanvantri Library at the University of Jammu. Quantitative techniques were employed to investigate how effectively e-resources are being used remotely. The study focused on users’ assessments of e-resources and the satisfaction level derived from them. The Technology Acceptance Approach (TAM) model is used to explore the level of adoption of e-resources through remote access in two dimensions, i.e., PU and PEU. The results revealed a positive attitude towards e-resources and moderately adopted 2.05 ± .83, the remote access environment of the Dhanvantri library, where the average perceived usefulness is 2.97 ± 1.17, and the perceived ease of use is 2.58 ± 1.99. Consequently, TAM is significantly related to PEU [ χ2(12, 299) = 219.06, p<.001] and PU [χ2(10, 299) = 48.33, p<.001].